Brief on waqf, its substitution (Istibdāl), and selected resolutions of Islāmic Fiqh Academy India: a maqāṣid al-sharī’ah perspective - Ali, Mohammed Farid; U Tun Aung, Maulana Akbar Shah; Gamon, Alizaman Dumangcag (IIUM Press, 2018)
Waqf is a charity in which corpus is maintained and the usufruct is given to the beneficiaries. The continuity of the usufruct depends on the maintenance and management of the corpus. One of the modes used both in classical and modern times to maintain waqf-properties is substitution of one waqf-property with another known as istibdāl. This paper reads into Istibdāl, selected resolutions of Fiqh Academy India and scrutinizes them under the Sharī’ah objectives of waqf and tabarru‘āt (donation). The finding shows that modes of Istibdāl permitted by Islāmic law realize the Sharī’ah objectives of waqf concomitantly. Modes which were not permitted oppose the objectives of the Sharī’ah. This work is a potential guide for institutions and committees involved with the development of waqf-properties using innovative financing modes.